(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Purwanto RH, Mulyana B, Sari PI, Hidayatullah MF, Marpaung AA, Putra ISR, Putra AD. 2021. The environmental services of Pangarengan mangrove forest in Cirebon, Indonesia: conserving biodiversity and storing carbon. Biodiversitas 22: 5609-5616. Pangarengan mangrove forest in Cirebon, Indonesia, plays a vital role in providing ecosystem services, such as conserving biodiversity and storing carbon. The area of the Pangarengan mangrove forest is relatively small, but it is home to diverse flora and fauna. Also, it can mitigate climate change by storing carbon. Unfortunately, no specific records exist on biodiversity and carbon stock in the Pangarengan mangrove forest. This study aimed to record the diversity of flora and fauna of the Pangarengan mangrove using a survey approach and to estimate its carbon stocks using a non-destructive sampling method, except for seedlings, on 78 sampling plots, distributed randomly along the banks of the Cipaluh River. The results revealed that the flora consisted of 24 species, and the fauna was composed of 12 species. The mangrove species in the Pangarengan mangrove forest was dominated by Rhizophora mucronata. The carbon stocks varied among species or the life stages of plants (seedlings, saplings, poles, and trees). The carbon stock of Avicennia marina trees was the highest (110.810 MgC/ha), and the lowest was the seedlings of the Avicennia alba (0.005 MgC/ha). Furthermore, the interpretation of the images showed that the Pangarengan mangrove forest area is 21.5 ha. The mangrove forest is located in the coastal area of the Java Sea, 2.4 km from the residential area of Pangarengan village. It is crucial to preserve the Pangarengan mangrove forest because it functions as a source of biodiversity and carbon storage.